Escrevendo-se na cidade: ExueoGuia afetivoda periferia, de Marcus Vinicius Faustini - Vinicius Mariano de Carvalho (Estudos de Literatura Brasileira Contemporânea)
n the preface to the inaugural book of Marcos Vinicius Faustini, Luiz EduardoSoares says: ―The movement of Faustini’stext is sinuous as his urbantrajectories, and devious as his existential journey‖. This statement opens quiteprovocative perspectives on the phenomenological conception presentFaustini’s narrative. This paper analyzes how Faustini creates a narrator/actorwho, instead of writing the city, writes himself on it. With this performativemovement, the author contrasts the common tendency to divide the urban spacein center x periphery, city x slum, hill x asphalt. Using the mythology of Afro-Brazilian religions, I analyze how the narrator/actor ofGuia Afetivo da Periferiaincorporates features of the Orixá Exú and consubstantiates the cityphenomenologically.